Differences in pyrolysis behavior and volatiles of tar-rich coal with various origins - Qingmin Shi; Xinyue Zhao; Shuangming Wang; Hongchao Zhao; Ruijun Ji; Chunhao Li; Bingyang Kou; Jun Zhao (Fuel Processing Technology)
Abundant in northwest China, tar-rich coal exhibits significantly diverse pyrolysis behaviors depending on its origins. For low-temperature pyrolysis experiments, three coal-forming environments were selected: limno-telmatic (Sample S-1), wet forest swamp (Sample O-1), and dry forest swamp (Sample O-2). The pyrolysis behavior and the molecular structure evolution were analyzed through thermogravimetric, Fourier transform infrared spectroscopy, gas chromatography, and gas chromatography-mass spectrometer. The findings revealed three stages of pyrolysis behavior in tar-rich coal. Compared to others, S-1, formed in a stronger reducing environment, had a 17 °C lower initial pyrolysis temperature, a 5 °C lower peak reaction temperature, and a 20 % higher weight loss. The reason for S-1 had more bonds with lower energies, accounting for 76 % of the total fragmented bonds, which was 10 % higher than others. Moreover, S-1 contained more highly reactive molecular structures and exhibited higher thermal decomposition. The variations in molecular structure and pyrolysis behavior were reflected in the pyrolysis products, with S-1 showing higher yields of tar, gas, and water, but lower semi-coke. Specifically, it had 2 % higher aliphatics and aromatics and 4 % fewer oxygenated compounds, along with higher levels of CO and CO2, and lower amounts of H2, CH4, and CnHm in volatiles.